2009
DOI: 10.1007/s12195-009-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stability Determines Stress Fiber and Focal Adhesion Orientation

Abstract: It is well documented in a variety of adherent cell types that in response to anisotropic signals from the microenvironment cells alter their cytoskeletal organization. Previous theoretical studies of these phenomena were focused primarily on the elasticity of cytoskeletal actin stress fibers (SFs) and of the substrate while the contribution of focal adhesions (FAs) through which the cytoskeleton is linked to the external environment has not been considered. Here we propose a mathematical model comprised of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…The Poisson constant of basic mechanics describes how stretched objects get thinner, i.e., are compressed. Theoretical modeling of cytoskeleton reorganization under stretching has shown that the cytoskeleton resists loading mainly by changing the orientation and spacing of actin filaments (33). Longitudinal stretching along fibers causes reduction in the spacing between them (31).…”
Section: Discussionmentioning
confidence: 99%
“…The Poisson constant of basic mechanics describes how stretched objects get thinner, i.e., are compressed. Theoretical modeling of cytoskeleton reorganization under stretching has shown that the cytoskeleton resists loading mainly by changing the orientation and spacing of actin filaments (33). Longitudinal stretching along fibers causes reduction in the spacing between them (31).…”
Section: Discussionmentioning
confidence: 99%
“…7,11,62,64,67,69 While each model has provided insight into the process of stretchinduced stress fiber reorganization, only a few of these models are capable of addressing the effects of strain rate. Wei et al 69 proposed a chemo-mechanical model in which cells initially devoid of stress fibers quickly formed stress fibers oriented in the direction of least fiber shortening, i.e.…”
Section: Strain Rate-dependent Stress Fiber Reorientationmentioning
confidence: 99%
“…To address a biomechanical issue, mathematical models help elucidate the complex relations between SFO and different patterns of stretch (De et al, 2007, Deshpande et al, 2006Hsu et al, 2009;Stamenović et al, 2009). Based on different criteria, such as maintaining local strain in the surrounding matrix or SF, or attaining a global minimum energy, different models predicted that SF contractility, Poisson's ration of the substrate, or the strain frequency are the predominant parameters controlling SFO response to the exogenous uniaxial stretch, respectively.…”
Section: Introductionmentioning
confidence: 99%